1998
DOI: 10.2527/1998.762528x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mechanical strength of intramuscular connective tissue during postmortem aging of beef.

Abstract: We studied changes in mechanical strength during postmortem aging of bovine semitendinosus muscle using intramuscular connective tissue (IMCT) preparations from muscle stored at 4 degrees C. In the preparation, muscle fiber elements were removed, leaving a virtually intact structure of the endomysium and perimysium. The shear-force value of the IMCT preparation remained unchanged up to 10 d postmortem and decreased linearly thereafter. The yield of the perimysial fraction, which was measured as an indicator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 20 publications
3
40
0
2
Order By: Relevance
“…When shear force values were compared to the structural changes occurring in the muscle, tenderness increased rapidly during the first 10 days, and then gradually increased during the remaining 18 days. Similar results were reported by Nishimura et al (1998), but neither study could identify the primary cause of the connective tissue degradation. Greaser (1997) Feidt et al (1996) reported increased levels of free hydroxyproline in postmortem muscle, an amino acid found only in collagen and elastin.…”
Section: Connective Tissue Degradationsupporting
confidence: 82%
See 1 more Smart Citation
“…When shear force values were compared to the structural changes occurring in the muscle, tenderness increased rapidly during the first 10 days, and then gradually increased during the remaining 18 days. Similar results were reported by Nishimura et al (1998), but neither study could identify the primary cause of the connective tissue degradation. Greaser (1997) Feidt et al (1996) reported increased levels of free hydroxyproline in postmortem muscle, an amino acid found only in collagen and elastin.…”
Section: Connective Tissue Degradationsupporting
confidence: 82%
“…Therefore, it was reasoned that the release of hydroxyproline in postmortem muscle might be attributed to the breakdown of collagen molecules (Feidt et al, 1996). Nishimura et al (1995Nishimura et al ( , 1998 attributed the initial rapid decline in toughness to myofibrillar changes within the muscle, and the later, gradual decline in toughness to connective tissue degradation, emphasizing this process as a key component of extended postmortem aging.…”
Section: Connective Tissue Degradationmentioning
confidence: 99%
“…Although proteolytic weakening of connective tissue has been reported (Stanton and Light 1990;Nishimura et al 1998), it is generally accepted that, relative to the myofibrillar component, the post-slaughter changes in the connective tissue contribution to toughness are quite small.…”
Section: Post Mortem Muscle Biochemistrymentioning
confidence: 99%
“…Myofascial force transmission is so named because there is ample evidence that force is not exclusively transmitted to the origin or insertion of the muscle fibers (myotendinous force transmission), but in addition, force is transmitted onto the endomysium (Street, 1983;Street and Ramsey, 1965) and from there further onto the whole intramuscular connective tissue stroma, consisting of the intricate network of endomysial perimysial and epimysial tubes or tunnels (Jarvinen et al, 2002;Nishimura et al, 1994Nishimura et al, , 1996aNishimura et al, ,b, 1999Nishimura et al, , 1998Nishimura et al, , 1997Nishimura et al, , 1996cPurslow and Trotter, 1994;Trotter and Purslow, 1992), within which the muscle fibers and fascicles and also the whole muscle are active (see also Fig. 1).…”
Section: Intramuscular Myofascial Force Transmissionmentioning
confidence: 99%